Data analysis and management system design of contaminated site based on intelligent data acquisition vehicle and 5G communication. (19th July 2020) - Zhang, Shuyuan; Cheng, Quanguo
Summary: The integration of information is an important feature of the fourth industrial revolution, and the interconnection of all things is permeating the world at an amazing speed. In 2019, 5G communication technology has started to be commercialized in the world. Its high transmission speed, low delay, high reliability, and other technical features provide technical support for the application of intelligent driving vehicle technology. In a specific environment, such as tunnels, deserts, and dangerous areas, if the traditional manual method is used to collect environmental data, it is difficult to achieve, and the operability is not strong, and even there will be security risks. Intelligent car has intelligent mechanism such as identification, detection, and environmental data collection, it can replace human work in bad conditions, and it has broad application prospects. Compared with the traditional manual acquisition method, the intelligent data acquisition vehicle is more operable and practical, the difficulty of environmental data acquisition is greatly reduced, and the implementation cost is generally lower than the manual acquisition method. In this paper, an intelligent collection vehicle system based on 5G communication technology is constructed and applied to the data analysis of polluted sites. At the same time, this paper constructs a data analysis and management system based on hardware structure. The experimental results show that the method proposed in this paper can effectively analyze the data of polluted sites and has strong practicability. Abstract : In this paper, an intelligent collection vehicle system based on 5G communication technology is constructed and applied to the data analysis of polluted sites. At the same time, this paper constructs a data analysis and management system based on hardware structure. The experimental results show that the method proposed in this paper can effectively analyze the data of polluted sites and has strong practicability.